Use and perceived benefits of mouthwash among Malaysian adults: An exploratory insight - Mitha, Shahid; Elnaem, Mohamed Hassan Abdelaziz; Koh, Michelle; Ching, En; Babar, Muneer Gohar; Siddiqui, Jamshed; Jamshed, Shazia Qasim (Academy Of Advanced Dental Research, 2016)
Objectives: The purpose of the current research is to comprehend the use as well as the perception of mouthwash benefits among Malaysian adults in Selangor state, Malaysia.